PENCEMARAN NAMA BAIK: KAJIAN LINGUISTIK FORENSIK - Mintowati Mintowati (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
This paper aims to discuss lingual data of defamation cases based on analysis, lexical semantics, grammatical semantics, and pragmatic analysis (speech acts) which are part of linguistic forensic studies. From the lingual data on defamation that has been analyzed based on the three points of view, the following findings are obtained: (1) based on the lexical semantic analysis found the lexical meaning / meaning of word denotation; (2) based on the grammatical semantic analysis, the meaning of phrases, sentences, and discourse in accordance with the intended by the speaker; (3) there are speech acts of illocution and expressive perlokusi, both from speakers and partners said. Based on the results of the analysis it can be concluded that a speech is classified as defamation and this can be utilized by the investigator as one of the basis for the preparation of the investigation event (BAP) as well as the decision making for the legal sanction for the defamation perpetrator